Evaluation of the use of different lamps in light trap model for insect capture - Pelli, Afonso; de Oliveira , Amanda Rodrigues; Gonçalves, Bruna Vilarinho; do Santos Júnior, Carlos Paulino; Rezende, Eliana Mendes de Sousa; dos Santos, Evylin Sousa; Sartori, Fernanda Coutinho; Brunelli, Giuliana Gulhote; Pereira, Hellen Sant'Ana; de Lima, Ian Kolossowski Martinez; Cardoso, Isabela David; Tofanin, Juliana Soares; et al. (Seven Editora, 2023)
Aware of the importance that insects have, as well as their influence, both in ecosystems and human activities, the group has always received prominence in several areas of knowledge. In order to enjoy this immense diversity, the first step is to recognize and classify them. For this, a light trap model was elaborated, using three different lights (black, cold white and warm white). The pitfall-style trap, which in addition to the lights contained a container with alcohol and detergent, was properly assembled. Insects were collected, analyzed and identified. These processes allowed analyzing the efficiency of the trap with different lamps in the capture of insects, as well as the Orders to which they belong. In the end, it was observed that the Order of highest index in the analysis was Homoptera, and that the trap whose light source was black light was the most efficient in quantitative capture, with a total of 497 insects, followed by warm cold white light, respectively. DOI: https://doi.org/10.56238/methofocusinterv1-051